2009
DOI: 10.1002/tea.20309
|View full text |Cite
|
Sign up to set email alerts
|

Bridging scientific reasoning and conceptual change through adaptive web‐based learning

Abstract: This study reports an adaptive digital learning project, Scientific Concept Construction and Reconstruction (SCCR), and examines its effects on 108 8th grade students' scientific reasoning and conceptual change through mixed methods. A one-group pre-, post-, and retention quasi-experimental design was used in the study. All students received tests for Atomic Achievement, Scientific Reasoning, and Atomic Dependent Reasoning before, 1 week after, and 8 weeks after learning. A total of 18 students, six from each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 63 publications
2
48
0
4
Order By: Relevance
“…The findings from the research studies showed the importance of a cognitive domain on learners' process of conceptual change toward better conceptual understanding in science (e.g., She 2004;She and Liao 2010;Srisawasdi et al 2013;Srisawasdi and Kroothkeaw 2014). However, how conceptual change happens or how students progress during conceptual understanding in science is a somewhat blurry picture for many science educational researchers.…”
Section: Enhancing Science Learning Through Conceptual Changementioning
confidence: 99%
See 1 more Smart Citation
“…The findings from the research studies showed the importance of a cognitive domain on learners' process of conceptual change toward better conceptual understanding in science (e.g., She 2004;She and Liao 2010;Srisawasdi et al 2013;Srisawasdi and Kroothkeaw 2014). However, how conceptual change happens or how students progress during conceptual understanding in science is a somewhat blurry picture for many science educational researchers.…”
Section: Enhancing Science Learning Through Conceptual Changementioning
confidence: 99%
“…Through this taxonomy, the students' cognitive processes of conceptual change were captured. Moreover, in an attempt to quantify the mechanical change of students' conceptual understanding, She and Liao (2010) proposed the idea for analysis of conceptual change as follows: (a) progress (PG); (b) maintain-correct (MTC); (c) maintainpartial correct (MTPC); (d) maintain-incorrect (MTIC); (e) retrogression (RTG). Researchers argue that actively engaging students in the process of conceptual change are important for development of conceptual understanding in science.…”
Section: Enhancing Science Learning Through Conceptual Changementioning
confidence: 99%
“…The authors found a strong positive relation between students' scientific reasoning skills and their conceptual knowledge gains. Liao and She (2009), and She and Liao (2010) also found that 8 th grader high scientific reasoners' conceptual knowledge gains were higher than other 8 th graders after a web-based learning unit. Similarly, Ates and Cataloglu (2007) investigated the relation of students' scientific reasoning with their conceptual knowledge and problemsolving skills in an introductory mechanics course.…”
Section: Scientific Reasoning and Conceptual Knowledgementioning
confidence: 94%
“…More importantly, scientific reasoning explained more of the variance in student achievement scores than self-efficacy. Similarly, She and Liao (2010) examined the relation of 8 th graders' scientific reasoning and conceptual knowledge with their achievement on a unit about atoms. Authors found that most of the variance in students' achievement was explained by their scientific reasoning scores.…”
Section: Scientific Reasoning and Achievementmentioning
confidence: 99%
See 1 more Smart Citation